(untitled) (Rajarshi Janak University Research Journal, 2025)
Although the government of Nepal recognizes nongovernmental organizations (NGOs) as development partners, their perspectives on regulations remain understudied. Using a convergent mixed methods approach, this study investigates the perceptions of NGOs regarding the regulatory framework. Data were collected through a survey questionnaire with 216 NGO officials and key informant interviews with 11 NGO executives on their perceptions of the regulatory environment, institutional environment, and regulatory compliance. Descriptive statistics and independent t-tests were employed to analyze quantitative data, and qualitative data were analyzed thematically based on Braun and Clarke’s framework, whereas Fetters et al.’s framework was employed in data integration. The findings illustrated that both centrally and locally based NGOs perceived government regulatory framework as satisfactory on paper and restrictive at the operational level due to the personal interests of individuals in authority, noncompliance with government rules, and the dominance of informal rules in regulatory agencies. The study’s implications are discussed to suggest government, policymakers, and donors.